Assessing the Effectiveness of Foreign AID and Its Mobilization in Nepal - Kharel, Khom Raj; Adhikari, Dipak Bahadur; Khadka, Ramesh Bahadur (Janapriya Journal of Interdisciplinary Studies, 2021)
This paper has focused on the effectiveness of foreign aid for economic progress of developing nations with emphasis of Nepal. Nepal has the momentum of uplifting developing nations from the least developed countries by accepting foreign aid through the effective mobilization. This study has been conducted by using the historical data over the period of 1992/93-2019/20. The paper has argued that the concept of granting and withholding of foreign support useful resources changed into and nevertheless getting mobilization to steer the macroeconomic policies of growing developing nations. The paper has argued that foreign aid effectiveness reflected in terms of improving people’s livelihood with better status. To measure the effectiveness of the foreign aid, the simple statistical tools have been applied. The present study has found that foreign aid granted to overnment of Nepal and enhanced great effort in the economy but it changed into positive prerequisites with the aid of using donors and debt which impacted negatively to its motive ensuing Nepal’s government turning into depending on foreign aid effectiveness mobilizations.